Exploring Solvent Stability against Nucleophilic Attack by Solvated LiO2− in an Aprotic Li-O2 Battery. Issue 2 (1st January 2017) - Chau, Vincent K. C.; Chen, Zhening; Hu, Hao; Chan, Kwong-Yu
Abstract : Solvent degradation due to reactivity with various oxygen species is one of the most important issues in aprotic Li-O2 batteries. Recently, a more complete mechanism for discharge in an aprotic Li-air battery has been proposed, which accounts for the formation of solvated peroxides by disproportionation. In the present work, nucleophilic attacks by one of these solvated peroxides, LiO2 − (solv) on some commonly used solvents in aprotic Li-air batteries, including acetonitrile (MeCN), 1-methyl-2-pyrrolidone (NMP), dimethoxy ethane (DME), and dimethyl sulfoxide (DMSO) have been explored by calculating the reaction and activation free energies using density functional theory (DFT) method. The results show that despite demonstrating strong stability against nucleophilic attacks by O2 − (solv), these solvents are susceptible to nucleophilic attacks by LiO2 − (solv). The results provide new insight for identifying stable solvents in aprotic Li-O2 batteries.